O antifascismo nas páginas do periódico O Homem Livre (1933-1934) - Heckler, Bruno Mateus (2023)
The victory of the Allied1 countries over the Axis2 countries and the consequent end of the Second World War (1939-1945) was seen by many as a definitive blow against Nazi-fascism, after all, the horrors of the conflict were revealed to the world, so that a Such an experience, in addition to being sufficiently traumatic, had a pedagogical character and contained, for those who believed in this narrative, a hope synthesized around the belief that we would not be able to let any form of fascism gain momentum again. However, to paraphrase Bertold Brecht (1898-1956), and his most famous phrase, “the bitch of fascism is always in heat”. Classic fascism, in fact, may have died in 1945, however, circumstances aside, ideas identified with fascism continued to be an inspiration for social groups, institutions, political movements and individuals, even if, sometimes, these did not even have greater theoretical knowledge on the topic. More recently, with the emergence of Alt-Right3 and the rise of far-right political movements around the world, the concept of fascism has become more frequently addressed in public debate. In the Brazilian context, the rise of Jair Messias Bolsonaro, elected president in 2018, triggered several questions regarding the nature of his ideas and those of his followers, whose slogans “God, Country and family”4 have been abundantly used since the military started to occupy the news.